Registration of ATx3363 and BTx3363 Black Sorghum Germplasms. Issue 3 (1st July 2013) - Rooney, William L.; Portillo, Ostilio; Hayes, Chad
Abstract : The sorghum [ Sorghum bicolor (L.) Moench] germplasms ATx3363 (Reg. No. GP‐731, PI 668028) and BTx3363 (Reg. No. GP‐732, PI 668029) were developed and released by Texas AgriLife Research sorghum breeding program in 2012. Tx3363 is a grain sorghum seed parent designed to produce a very dark‐colored (i.e., black) grain hybrid in combination with Tx3362. BTx3363 was developed with pedigree selection methods and the male sterile version (ATx3363) was developed via backcrossing using ATx623 as a source of A1 cytoplasm. Grain produced from the combination of Tx3363/Tx3362 has potential use and application as a natural colorant and source of antioxidants. The color is associated with high levels of 3‐deoxyanthocyanins in the pericarp of the grain. Therefore, they have application as natural colorants in many processed food products. Because these compounds are present in the pericarp, they are easily concentrated by simply decorticating the grain and collecting the resulting bran. Tx3363 sorghum germplasm can be used as a seed parent to produce hybrids rich in 3‐deoxyanthocyanins or as a breeding parent to produce additional lines with this unique characteristic.